(untitled) (Journal of Health, Population and Nutrition, 2011)
A 22-year old woman visited the LAMB Hospital, Parbatipur, Dinajpur, Bangladesh, in February 2010, with exertional dyspnea for three weeks. She had had a normal vaginal delivery four months ago; 2-dimensional echocardiogram showed severe left ventricular dysfunction and biventricular thrombi, which resolved without complications after anticoagulation. Biventricular thrombosis with peripartum cardiomyopathy is quite a rare finding, and its clinical course and proper management is not known. No such case has previously been reported in Bangladesh. Key words: Biventricular thrombi; Case studies; Peripartum cardiomyopathy; Bangladesh DOI: http://dx.doi.org/10.3329/jhpn.v29i2.7862 J HEALTH POPUL NUTR 2011 Apr;29(2):178-180